A case of premortem diagnosis of cardiac tamponade due to pericardial metastasis of rectal cancer. Issue 4 (20th April 2023) - Takano, Yuki; Mazaki, Junichi; Tasaki, Koichiro; Udo, Ryutaro; Tago, Tomoya; Okazaki, Naoto; Kasahara, Kenta; Kuwabara, Hiroshi; Enomoto, Masanobu; Isizaki, Tetsuo; Matsubayashi, Jun; Nagao, Toshitaka; et al.
Abstract: Colorectal cancer rarely develops pericardial metastasis, and it is an extremely rare case that cardiac tamponade due to the metastasis of colorectal cancer during life. Our case is of a 50-year-old woman who underwent laparoscopic lower anterior resection for the rectal cancer with lung metastasis 4 years ago developed cardiac tamponade due to pericardial metastasis of rectal cancer. We performed pericardiocentesis as a temporary life-saving procedure, but pericardial fluid re-accumulated within a few days. She died 23 days after admission. When a patient with advanced colorectal cancer complains dyspnea, we should consider the pericardial metastasis, and perform the proper treatment as this case.